Annual World Bank Conference on Development Economics, 2001/2002 edited by Boris Pleskovic and Nicholas Stern.. - Stern, N. H.; Pleskovic, Boris. (World Bank: Oxford University Press, 2002)
"The 13th annual conference, held in May 2001, concentrated on the current thinking in development policy and the implications for the global economy with a particular focus on the two important and controversial themes of globalization and health."